Masculinity Of Male Cosmetics Online Advertising (Barthesian Semiotic Analysis) - Kholidatul Imaniyah (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Online men's cosmetic advertisements not only sell beauty products but also redefine the concept of masculinity by promoting self-care without losing manliness. This research aims to uncover myths of masculinity in specific men's cosmetic advertisements from a Barthesian semiotic perspective. This study is a qualitative research type. The data in this research consist of sentences contained in men's cosmetic advertisements, and the data source is images/advertisements of men's cosmetics online. The method used in data collection is the free observation method. Researchers browse men's cosmetic advertisements online, then listen to the messages contained in them. After the data is collected, the researcher reduces and classifies it based on its type. Subsequently, the researcher analyzes the data, then interprets it. The data is studied using Barthesian semiotics by viewing advertisements as mythical discourse that has meanings, forms, and concepts of masculinity. The results show that men's cosmetic advertisements tend to build the myth of metrosexual masculinity. Additionally, they also advocate for environmentally friendly products and address ecofeminist issues.